The beauty in imperfection: how naturalness cues drive consumer preferences for ugly produce and reduce food waste - Xiao, Meizhen; Jiang, Yi; Cao, Binbin (Frontiers in Sustainable Food Systems, 2023)
An important reason for food waste is the rejection of ugly produce by consumers. Most previous research has examined the absolute negative impacts of ugly produce on consumers’ preferences, no research has examined the conditions in which consumers prefer ugly (vs. typical) produce instead.This research investigates the circumstances under which these aesthetic imperfections become advantageous. Utilizing a between-subject design across two randomized experiments, we find that cues signaling naturalness can significantly alter, and even invert, consumer aversion to ugly produce. This study further identifies the mediating role of subtyping effects in this preference reversal. Grounded in schema incongruity theory, the findings suggest that naturalness cues help consumers reconcile the incongruous attributes of ugly produce, thereby enhancing its appeal. This study contributes to a nuanced understanding of consumer behavior towards ugly produce and offers actionable insights for reducing food waste.